Analisis Kestabilan Mobil Hemat Energi Adyatma Pada Kondisi Jalan Berbelok - muri febrian (Department of Mechanical Engineering, Universitas Andalas, 2022)
The Adyatma Urban energy-efficient car is one of the works of the Riau University Mechanical Engineering team. This car has been designed and built in 2020 to be included in the 2020 Energy Efficient Car Contest (KMHE). At the Energy Efficient Car Contest (KMHE), incidents often occur in the form of a vehicle rolling over when turning. This can happen because the level of security of a vehicle is not good, such as the stability of the vehicle when turning. This research was conducted by analyzing the stability of the energy-saving Adyatma urban car when turning. The study was conducted using a quasi-dynamic calculation method which analyzes vehicles that move dynamically, but are analyzed as if they were in static conditions. Performed on dry and wet asphalt road types, with variations in speed of 30 km/hour, 40 km/hour, 50 km/hour and 60 km/hour, with turning radius 4.5 m, 5 m, 5.5 m and 6 m . After doing research on the Adyatma Urban car, the best stability was obtained when the vehicle was traveling on a flat road. Where for the maximum speed limit of the front wheels and rear wheels so as not to skid on dry asphalt and wet asphalt road types, respectively 21.53 km/hour and 18.75 km/hour and 21.2 km/hour and 18.54 km / h with a large turning angle of 19.35 °. The maximum speed limits to prevent rolling over on the front and rear wheels are 32.76 km/h and 45.05 km/h, respectively, with a turning angle of 19.35°.